Strengthening Digital Literacy in Elementary Schools to Prepare Students for the Society 5.0 Era - Sintawati Liafitri; Nur Aisyah Kusuma Maharani; Tyas Nur Handayani; Kartika Yuni Purwanti (International Forum of Researchers and Lecturers, 2026)
The rapid convergence of digital technology and everyday human life in the Society 5.0 era requires elementary education to equip young learners with both technical competence and strong character. This study examines how digital literacy can be strengthened in elementary schools to prepare students for the challenges and opportunities of the Society 5.0 era, while simultaneously reinforcing character values such as responsibility, honesty, and empathy. Using a qualitative descriptive method supported by a systematic review of national and international publications from the last five years, this study analyzes the strategies, challenges, and outcomes of digital literacy integration in primary education. The findings indicate that effective digital literacy strengthening requires synergy among teachers, parents, and the school environment, supported by curriculum integration, habituation of ethical digital behavior, and the development of teacher digital competence. The study also finds that digital literacy cannot be separated from character education, since both are needed to produce a generation capable of using technology responsibly and ethically. A comparative analysis with studies from other countries shows similar overall patterns but also context-specific challenges related to infrastructure, teacher readiness, and cultural values. This study concludes that strengthening digital literacy in elementary schools is a strategic effort to prepare a generation of digitally competent and morally grounded students who are ready to face the complexity of the Society 5.0 era.